Collection of materials on the experience of combat activities of the naval forces of the USSR : No. 8 Experience of Utilization of External Sea Lines of Communication in the Northern Theater (July 1941 to November 1943). - Gebhardt, James F.; translator. (Moscow : Directorate of the Naval Press of the People's Commissariate of the Navy of the USSR, 1944)
This study was published in 1944, and the document is one of a series of 39 such studies of various aspects of the performance of the Soviet Navy during the war. Contains the original document in Russian. Topics include: frontline situation of the forces of northern defensive region on the coast of Varangerfjord and Sredniy and Rybachiy Peninsula; commander's concept and operational plan; decision of the commander, northern fleet, and plan of joint operations with Karelian front for the liberation of the Soviet far north; preparation for execution of the assigned mission; execution of the assigned missions; and organization of command and control for combat and the accomplishment of coordination.